A Contextual Analysis on Social Media Updates: Genderlect in Focus - Feliciano, Geraldine; Escandallo, Jonelson C. (International Journal of Asian Education, 2024)
This qualitative, corpus-based, and contextual analysis approach aimed to give and provide the linguistic features and functions in male and female social media updates. The purpose of this study was to help the students assess the posts of social media users and to find out if there are linguistic features or linguistic functions found in their social media updates. In this study, there were a total of sixty-two (62) corpora taken from both male and female social media updates that are categorized into five linguistic features, including the intensifiers, tag questions, questions on declarations, lexical hedges, empty adjectives and six linguistic functions including the referential function, poetic function, emotive function, conative function, phatic function and metalingual function. Results revealed that in social media updates of males and females, linguistic features and functions are found by contextualizing their posts in the adopted linguistic frame of analysis. Also, it helps future English students know the linguistic features and linguistic functions as their basis, using other platforms for them to be responsible for posting online. It serves as their point of reference for the students and English instructors to unearth the linguistic aspect in social media, particularly in males and females.